Heterogeneus bodies, a university outreach experience to promote the acceptance of body diversity (Cuadernos de Extensión Universitaria de la UNLPam, 2025)
The article discusses the main characteristics of a university outreach project aimed at raising awareness about body discrimination and its psychosocial implications. Whith the aim of promoting acceptance of body diversity, activities such as film debates, workshops in primary schools, a day event at a secondary school, and audiovisual productions with nursing students were carried out. These actions sought to challenge weight-centric discourses on health, make visible the impacts of stigmatization, and promote inclusive attitudes. The project integrated teaching, research, and outreach, strengthening the connection between the university and the community. Through interdisciplinary activities, it emphasized the importance of addressing body discrimination from an empathetic perspective, recognizing the effects of social standards on self esteem and mental health.This approach promoted experiential learning by involving students in the creation of educational materials and community actions. Despite economic and logistical limitations, the project reached approximately 550 primary school students, 50 secondary school students, and 300 university students, fostering debates and reflections on body diversity. The initiative underscores the significance of university outreach as a tool to create social impact and advance toward a more equitable and inclusive society.
Keywords: body image; children; weight prejudice; risk